Aligning Composed Query with Image via Discriminative Perception from Negative Correspondences - Wang, Yifan; Huang, Wuliang; Yuan, Chun (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
The task of composed image retrieval aims to match the multi-modal query composed of a reference image and a modification sentence with the target image. Most current approaches narrow the distances between the composed queries and targets by investigating matched correspondences in positive triplets. Nevertheless, they are inclined to exhibit heavy reliance on partial correlations. As the negative correspondences are underestimated, semantic clues that distinguish the target from mismatched candidates are obscured by incomplete associations. Moreover, the correlations between the modification textual features and the visual variations from the reference to candidates are imperative to further strengthen the semantic discriminations. In this paper, we propose DIscriminative Perception from NEgative Correspondences (DIPNEC) to address the aforementioned issues. To encourage awareness of the differences between matched and mismatched correspondences, DIPNEC introduces optimal transport with semantic preservation for reassignments on hard negative triplets. Besides, Difference Quantization Alignments (DQA) and Composed Word-level Alignments (CWA) jointly determine the matching scores between multi-modal queries and candidates. Specifically, DQA concentrates on the correlations of textual features with source-to-target visual differences, and CWA further emphasizes the differentiated semantics. DIPNEC has demonstrated competitive performances on the experimental results and ablation studies on widely-used datasets FashionIQ and CIRR.